2021
DOI: 10.1021/acs.jpcc.1c08924
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Catalytic Activity of Size-Specific Triphenylphosphine-Ligated Gold Nanoclusters in the Electrocatalytic Hydrogen Evolution Reaction

Abstract: Hydrogen production via electrocatalytic water splitting has attracted growing attention as an alternative renewable and clean energy source. Size-specific gold nanoclusters and complexes (AuNCs) can serve as models for investigating the catalytic behavior toward the hydrogen evolution reaction (HER) at the atomic level. This work is focused on exploring the factors influencing the catalytic activity of phosphine-ligated AuNCs as electrocatalysts for improving HER performance using Au101(PPh3)21Cl5, Au9(PPh3)8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…[ 251e ] Further reports of XPS studies performed to examine the electronic structure of gold–phosphine clusters by different groups are available here. [ 28 , 251 , 252 , 258 , 267 ]…”
Section: Characterization Of Au Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 251e ] Further reports of XPS studies performed to examine the electronic structure of gold–phosphine clusters by different groups are available here. [ 28 , 251 , 252 , 258 , 267 ]…”
Section: Characterization Of Au Clustersmentioning
confidence: 99%
“…Strategies to prevent aggregation such as the use of large surface areas, highly porous supports, creation of defects, ultralow gold loading and introduction of functionalized sites have been reported. [ 250 , 258 , 406 ] Alotabi et al. recently demonstrated that deposition of a thin (1.1 nm) layer of Cr 2 O 3 onto Au 9 /TiO 2 inhibits agglomeration of gold clusters after ligand removal by heating.…”
Section: Perspective and Future Prospectsmentioning
confidence: 99%
“…Two of our previous publications were dedicated to the formation of AuNCs-rGO nanocomposites without AuNCs agglomeration. [25,42] The AuNCs-rGO were synthesised via mixing a methanol dispersion of AuNCs and rGO for 1 h at RT in the dark. We discovered that the GO reduction method under acidic pH (pH � 2) is crucial to avoid the agglomeration of AuNCs.…”
Section: Auncs-rgo Synthesismentioning
confidence: 99%
“…We have previously reported greater HER performance for Au 101 NC-rGO compared to Au 1 NC-rGO and Au 9 NC-rGO. [42] In order to compare our reported data to literature value, we must consider some limitations in doing so. Electrocatalysis is highly dependent on the geometry of the electrode and the loading of the catalyst.…”
Section: Oxygen Reduction Reactionmentioning
confidence: 99%
See 1 more Smart Citation